Performance analyses of an advanced heat pump driven fresh air handling system using active and passive desiccant wheels under various weather conditions. (September 2022) - Liu, Mengdan; Tu, Rang; Chen, Xianzhong; Wu, Zilei; Zhu, Jie; Yang, Xu
Highlights: Propose an advanced system (AS) to process fresh air using desiccant wheels and heat pump. Energy and exergy performances are studied under a wide range of ambient conditions. COP of the AS is 1.07 to 1.35 times higher than that of a typical traditional system (TS). Excluding the heat pump, total exergy destruction of the AS is 47–79% of that in the TS. Total thickness of the two desiccant wheels in the AS is 400 to 500 mm to maximize EER . Abstract: An advanced fresh air handling system is proposed and analyzed. The outdoor air is pre-dried at an enthalpy wheel by the return air, which is used to regenerate the dehumidification wheel. Performances of the advanced system were studied and compared with a typical traditional system under various weather conditions. The regeneration temperature, energy efficiency, exergy efficiency, and system coefficient of performance ( COPsys ) were used as performance indices. The results show that, compared with the traditional system, the advanced system can effectively reduce the regeneration temperature by a maximum of 19.3°C. Performances are much better under hot and humid working conditions. For the advanced system, the total exergy destruction of the two wheels and the sensible heat recovery unit is 47% to 79% of that of the traditional system. When a heat pump system is used to provide both heating and cooling, COPsys are from 3.93 to 6.68 for the traditional system and from 4.88 to 8.21 for the advanced system. Considering power consumptions of fans and the heat pump, the optimal total thickness of the two wheels is in the range of 400–500 mm for a wide range of working conditions.